Parent, Friend and Teacher Relationships Buffer against the Effect of Adverse Childhood Experiences and Mental Disorders among Adolescents in Urban Vietnam - Ngo Anh Vinh; Doan Thi Mai Thanh; Phi Duc Long (Journal of Affective Disorders Reports, 2024)
Objective: This study aimed to measure how these parent, friend and teacher relationships could mediate the associations between adverse childhood experiences (ACEs) and mental disorders. Method: A cross-sectional study was implemented on students at an urban multi-level school in Hanoi, Vietnam. A total of 1275 students were included in the study. The Depression-Anxiety-Stress Scale-21 items (DASS-21) and Adverse Childhood Experiences Questionnaire (ACE-Q) scales were used. The present study employed structural equation modelling (SEM) to investigate the potential mediation effects of different relationships on the associations between ACEs and mental health. Results: The rate of depression, anxiety and stress among students were 44.0 %, 35.6 % and 30.6 %, respectively. Overall, 19.7 % experienced one mental disorder, 15.2 % suffered two disorders and 20.0 % experienced three disorders. Parent-child, friend-friend and student-teacher relationships were determined to partly mediate the connections between ACEs and mental disorders among students. The mediating effects of the parent-child, friend-friend and student-teacher relationships accounted for 13 %, 4.4 % and 5.8 % of the total effect, respectively; and 15 %, 4.6 % and 6.1 % of the direct effect, correspondingly. Conclusion: This study highlighted that receiving good parent-child, friend-friend and student-teacher relationships independently affected adolescents’ mental health, as well as buffered the effect of ACEs on mental disorders.